The Migration of an Angular Pregnancy to a Centric Position: A Case Report. (March 2020) - Fernandez, Carlos M.; Levine, Elliot M.; Tadros, Katherine; Shashoua, Abraham; Locher, Stephen
This case report illustrates the sequential imaging of pregnancy beginning as an angular pregnancy, and eventually descending to a centric location within the uterine cavity. This case also describes the potential benefit of three-dimensional sonography in the management of a pregnancy, initially recognized as an angular pregnancy.